2010
DOI: 10.1002/pnp.153
|View full text |Cite
|
Sign up to set email alerts
|

SNRI‐NaSSA combination therapy for treatment‐resistant depression

Abstract: Although more quality research is required to inform clinical practice, serotonin‐noradrenaline reuptake inhibitor ‐ noradrenaline and specific serotonergic antidepressant (SNRI‐NaSSA) combination therapy shows promise for treatment‐resistant depression. Here, Dr Pandarakalam discusses the rationale behind the use of this combination and some of the evidence gained so far for its efficacy. Copyright © 2010 Wiley Interface Ltd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Although clozapine is considered the gold standard treatment for TRS, other antipsychotic medications may be suitable alternatives in specific cases. The British Journal of Medical Practitioners suggested that combinations of antipsychotics such as olanzapine and amisulpride might be effective in cases where clozapine is unsuitable [ 61 ]. Additionally, various augmentation strategies, including other antipsychotics, mood stabilizers, benzodiazepines, lithium, electroconvulsive therapy, and repetitive transcranial magnetic stimulation, have been used, although there is a lack of strong evidence for these interventions [ 61 ].…”
Section: Management and Prevention Of Agranulocytosis During Clozapin...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although clozapine is considered the gold standard treatment for TRS, other antipsychotic medications may be suitable alternatives in specific cases. The British Journal of Medical Practitioners suggested that combinations of antipsychotics such as olanzapine and amisulpride might be effective in cases where clozapine is unsuitable [ 61 ]. Additionally, various augmentation strategies, including other antipsychotics, mood stabilizers, benzodiazepines, lithium, electroconvulsive therapy, and repetitive transcranial magnetic stimulation, have been used, although there is a lack of strong evidence for these interventions [ 61 ].…”
Section: Management and Prevention Of Agranulocytosis During Clozapin...mentioning
confidence: 99%
“…The British Journal of Medical Practitioners suggested that combinations of antipsychotics such as olanzapine and amisulpride might be effective in cases where clozapine is unsuitable [ 61 ]. Additionally, various augmentation strategies, including other antipsychotics, mood stabilizers, benzodiazepines, lithium, electroconvulsive therapy, and repetitive transcranial magnetic stimulation, have been used, although there is a lack of strong evidence for these interventions [ 61 ]. It is also noted that combining depot antipsychotics with oral drugs from different classes is a generally accepted practice [ 61 ].…”
Section: Management and Prevention Of Agranulocytosis During Clozapin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Clozapine, approved for TRS, is vastly under-utilized, due to its blood monitoring requirement and side-effects (neutropenia, metabolic syndrome), and at least 30% of patients do not respond to clozapine. Other strategies to treat TRS, such as combining 2 APs are ineffective ( Elkis and Buckley, 2016 ; Nucifora, et al, 2019 ; Pandarakalam JP, 2019 ), as glutamatergic mechanisms have been shown to be involved in the etiopathogenesis of schizophrenia ( Schwartz, 2012 ; Egerton et al, 2020 ). This is supported by data from patients with TRS and first-episode nonresponders who demonstrate normal dopamine synthesis capacity ( Kim et al, 2017 ; Jauhar et al, 2018 ) but higher levels of glutamate in the anterior cingulate cortex ( Egerton et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%